2017
DOI: 10.1080/02640414.2017.1287933
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic power and energy expenditure in an international men’s hockey tournament

Abstract: The purpose of this study was to ascertain the typical metabolic power characteristics of elite men's hockey, and whether changes occur within matches and throughout an international tournament. National team players (n = 16), divided into 3 positional groups (strikers, midfielders, defenders), wore Global Positioning System devices in 6 matches. Energetic (metabolic power, energy expenditure) and displacement (distance, speed, acceleration) variables were determined, and intensity was classified utilising spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 29 publications
3
62
0
2
Order By: Relevance
“…While a metabolic power approach has been used previously in other sports (Polglaze et al, 2017;Coutts et al, 2015), we acknowledge the possible underestimation of EE during match play by employing this method (Highton et al, 2016;Buchheit et al, 2015). Furthermore, data were gathered from a small sample size from one female International Touch squad during a single tournament.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a metabolic power approach has been used previously in other sports (Polglaze et al, 2017;Coutts et al, 2015), we acknowledge the possible underestimation of EE during match play by employing this method (Highton et al, 2016;Buchheit et al, 2015). Furthermore, data were gathered from a small sample size from one female International Touch squad during a single tournament.…”
Section: Discussionmentioning
confidence: 99%
“…13.2 ± 3.2 Kcal•min -1 ; Highton et al, 2016), it possesses a stronger association with EE (r = 0.63) than other measures such as high-speed distance (r = 0.50) or Player Load™ (r = 0.37; Highton et al, 2016). Given this method has been employed with other non-contact team sports (Polglaze et al, 2017), the metabolic power model offers a useful approach to understand the energy demands of Touch.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when playing 6-in-9 days matches, field hockey players were able to maintain exercise intensity, without finding changes in players' physical demands as the tournaments progressed . Similarly, another study showed that field hockey players under the same congestion schedule context were capable of maintain their physical demands within and across matches (Polglaze, Dawson, Buttfield, & Peeling, 2017).…”
mentioning
confidence: 88%
“…The classification of intensity in team sport activity is most commonly made by categorising all movements into speed thresholds [3]. The total amount (absolute) of accumulated distance achieved and the frequency, distance, and time spent within each speed threshold is then determined [4].…”
Section: Introductionmentioning
confidence: 99%